Production of carbon molecular sieves from palm shell based activated carbon by pore sizes modification with benzene for methane selective separation - Adinata, D.; Daud, W.M.A.W.; Aroua, M.K. (Fuel Processing Technology, 2007)
Palm shell based activated carbon prepared by K2CO3 activation is used as precursor in the production of carbon molecular sieve by chemical vapor deposition (CVD) method using benzene as depositing agent. The influences of deposition temperature, time, and flow rate of benzene on pore development of carbon molecular sieve (CMS) and methane (CH4) adsorption capacity were investigated. The parameters that varied are the deposition temperature range of 600 to 1000 °C, time from 5.0 to 60 min, and benzene flow rate from 3.0 to 15 mL/min. The results show that in all cases, increasing the deposition temperature, time, and flow rate of benzene result in a decrease in adsorption capacity of N2, pore volume and pore diameter of CMS. The BET surface area of CMS (approximately 1065 m2/g) and the adsorption capacity of CH4 were at a maximum value at a deposition temperature of 800 °C, time of 20 min and benzene flow rate of 6 mL/min. The product has a good selectivity for separating CH4 from carbon dioxide (CO2), nitrogen (N2), and oxygen (O2).